RHETORIC AND NOVEL - Venus Brasileira Couy (Travessias, 2013)
The spread of the novel becomes possible with the invention of printing. What distinguishes the novels narrative and epic, in the strict sense, is the fact that the novel is essentially linked to the book. In the eighteenth century, in France, there were books allowed and prohibited, controlled by the police, provincial corporations and the Community of booksellers and printers of Paris. Seeking to establish itself, the novel uses inventiveness in order to give dignity to the fledgling genre, giving it utilitarian function and rhetorical effectiveness. The concern with the public, substancial in the rhetorics laws, becomes, in the eighteenth century, a major feature of the literature. At that time, the very nature of rhetoric, no longer understood as a compilation of rules, but rather as a persuasive force, is questioned. The novel, however, hardly fits in the schemes provided by rhetorical genres. It is in this context that philosophy in the alcove, Sades book, shows up and can be read, with a diverse and hybrid nature, making difficult to fit it into a genre. Sades novel, which is more like a play, is composed of seven dialogues, presenting a curious symmetry, organization and retreat.